A Survey on Security Threats and Attacks in Cloud Computing - Muthukumar, VP; Saranya, R (International Journal of Computer Sciences and Engineering, 2014)
Cloud computing is one of today's most exciting technologies due to its ability to reduce costs associated with computing while increasing flexibility and scalability for computer processes. During the past few years, cloud computing has grown from being a promising business idea to one of the fastest growing parts of the IT industry. IT organizations have expresses concern about critical issues (such as security) that exist with the widespread implementation of cloud computing. The security for Cloud Computing is emerging area for study and this paper provide security topic in terms of cloud computing based on analysis of Cloud Security threats and Technical Components of Cloud Computing.